PERAN LEMBAGA PENDIDIKAN ISLAM (MADRASAH) DALAM PERUBAHAN SOSIAL - Siti Asiah (Turats, 2020)
One of the educational institutions that cannot be ignored is Islamic religious education ormadrasas. Madrasas are one of the nation’s assets in developing human resources. Under the auspicesof the Ministry of Religion, “madrasas” have made a long history of ups and downs and contributionsto the progress of the state and nation. This study describes the role of Islamic education institutions(madrasas) in social change, which was carried out in several madrasas in the Bekasi Regency. Thisresearch is a library research with an educational and sociological approach. The results of the studyexplain that madrasas have several roles, including 1) Educational Roles. In this case, the madrasaas an Islamic educational institution is a place for transmitting knowledge, expertise, and behavior inaccordance with Islamic values and teachings so that madrasas can produce generations who havebroad insights not only in the Islamic sciences but also in general science. have faith and fear of AllahAlmighty and have noble character as a generation that can become the heir to the Prophet and theheir to the nation and state; 2). The Role of Brotherhood and Atonement. Through madrasas whereevery student can gain knowledge without distinction of class, race, ethnicity, and nation, and areonly bound by bonds of faith, madrasas can become social glue and the foremost fortress for effortsto create harmony between the people and the nation; 3) Madrasas act as social control. Religiousteachings by their adherents are considered as norms, so in this case, religion can function as socialcontrol individually or in groups. Likewise, madrasas can carry out their role as social control in themidst of this almost uncontrollable social change. 4). Madrasas can also play a role as a means oftransforming society. 5). Madrasas as filters and bulwarks of the negative impacts of social change.